A novel adaptive control method for induction motor based on Backstepping approach using dSpace DS 1104 control board. (1st February 2018) - Ben Regaya, Chiheb; Farhani, Fethi; Zaafouri, Abderrahmen; Chaari, Abdelkader
Highlights: A modified structure of the Backstepping nonlinear observer of the IM is presented. A new adaptive Backstepping rotor resistance observer is also presented. The proposed observer is validated by stimulation and experimentation using dSpace DS1104. A comparative study with the proposed algorithm and the MRAS observer is also made. Abstract: This paper presents a new adaptive Backstepping technique to handle the induction motor (IM) rotor resistance tracking problem. The proposed solution leads to improve the robustness of the control system. Given the presence of static error when estimating the rotor resistance with classical methods, and the sensitivity to the load torque variation at low speed, a new Backstepping observer enhanced with an integral action of the tracking errors is presented, which can be established in two steps. The first one consists to estimate the rotor flux using a Backstepping observer. The second step, defines the adaptation mechanism of the rotor resistance based on the estimated rotor-flux. The asymptotic stability of the observer is proven by Lyapunov theory. To validate the proposed solution, a simulation and experimental benchmarking of a 3 kW induction motor are presented and analyzed. The obtained results show the effectiveness of the proposed solution compared to the model reference adaptive system (MRAS) rotor resistance observer presented in other recent works.